Los siete modos de amor de Beatriz Nazareth (Teología, 2020)
The Seven degrees of Love by Flemish mystic and poet Beatrice of Nazareth forms, together with the work of two contemporary mystics, Hadewijch of Antwerp and Mechthild of Magdeburg, a chorus of female voices that stand out within the monastic theology of the XIII Century. Their works were written in vernacular language and so have adopted creative ways of courtly love poetry to express their experience of God. In continuity with the patristic tradition of the via amoris, Beatrice’s work focuses its speech in the desire of God. The aim of this paper is to demonstrate the relevance of this premodern medieval work on the horizon of a postmodernism in which desire and otherness are crossed. The kaleidoscopic conception of love of this text, opens horizons from which the question on the absolute can be made with the help and the experience and language of the mystics.
Keywords: Beatrice of Nazareth; Courtly Love Poetry; Monastic Theology; Desire of God; Desire and Otherness